2016
DOI: 10.1074/jbc.m116.721258
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Siglec-1 by Endotoxin Tolerance Suppresses the Innate Immune Response by Promoting TGF-β1 Production

Abstract: Sepsis is one of the leading causes of death worldwide. Although the prevailing theory for the sepsis syndrome is a condition of uncontrolled inflammation in response to infection, sepsis is increasingly being recognized as an immunosuppressive state known as endotoxin tolerance. We found sialylation of cell surface was significantly increased on LPS-induced tolerant cells; knockdown of Neu1 in macrophage cell line RAW 264.7 cells resulted in enhanced LPS-induced tolerance, whereas overexpression of Neu1 or tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
1
27
0
2
Order By: Relevance
“…We found that expression of sialylation was significantly decreased on the cells over-expressing Neu1 compared with empty vector control cells (Fig. 2B) and in our recently published data (13). The efficiency of the E. coli induced TLR4 endocytosis was significantly decreased on the cells over-expressing Neu1 compared with cells expressing empty vector, indicating that Neu1 plays an important role in E. coli -induced TLR4 endocytosis in D2SC/1 cells (Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…We found that expression of sialylation was significantly decreased on the cells over-expressing Neu1 compared with empty vector control cells (Fig. 2B) and in our recently published data (13). The efficiency of the E. coli induced TLR4 endocytosis was significantly decreased on the cells over-expressing Neu1 compared with cells expressing empty vector, indicating that Neu1 plays an important role in E. coli -induced TLR4 endocytosis in D2SC/1 cells (Fig.…”
Section: Resultssupporting
confidence: 85%
“…We have demonstrated that Neu1 plays a critical role in regulating Siglec-TLR interaction and endotoxemia (26). In order to determine whether Neu1 contributes to the regulation of E. coli -induced TLR4 endocytosis, we established D2SC/1 cell clones stably over-expressing shRNA for Neu1 as described in our recently published work (13, 26), treated these cells with E. coli at 37°C for one hour and examined for TLR4 surface levels. As shown in Figure 2A, increased expression of sialylation was observed on the cells over-expressing shRNA for Neu1, compared with the cells expressing scrambled shRNA, however, silencing of Neu1 in D2SC/1 cells has little effect on E. coli -induced TLR4 endocytosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, future studies would benefit from investigating TGF-β signaling in the brain following ethanol consumption. Futhermore, although there haven’t been any studies thus far investigating the interaction between TGFβ and Siglec-H, there is evidence for other Siglecs regulating TGFβ signaling in immune cells (Takamiya et al, 2013; Wu et al, 2016) and the addition of TGF-β1 to microglial cultures upregulates Siglech expression. Thus, the interaction between Siglec-H and TGFβ in microglia is also worthy of investigation.…”
Section: 3 Results and Discussionmentioning
confidence: 99%